Propulsive and braking contribution of the lower limbs, trunk, and upper limbs during underwater undulatory swimming calculated from vortices distribution: A simulation study - Tanaka, T.; Hashizume, S.; Kurihara, T.; Isaka, T. (Journal of Biomechanics, 2025)
Swimmers propel their bodies forward by generating vortices around themselves, which produce fluid force during underwater undulatory swimming (UUS). This study aimed to investigate the propulsive and braking contributions of the vortices of the lower limbs, trunk, and upper limbs during UUS. The kinematic data and three-dimensional digital model were collected from nine male swimmers. Vortex generation was obtained using computational fluid dynamics, and the fluid force of six vortices was determined from the vortex circulation, swimmers' segment velocity, and length. Foot vortices contributed 96.7 % to producing braking fluid force during the first half of the downward kick. Vortices of the feet and the ventral side of the trunk contributed 69.3 % and 58.8 % to producing the propulsive fluid force during the last half of the downward kick, respectively. During the first half of the upward kick, the vortices of the feet and ventral side of the trunk contributed to producing the 87.3 % of propulsive and 93.3 % of braking fluid force, respectively. During the last half of the upward kick, 63.1 % of propulsive and 86.9% of braking fluid forces were produced by vortices on the ventral side of the trunk and feet, respectively. Small fluid forces and contributions were detected for vortices of the arms, lower legs, dorsal sides of the shoulders, and waist. These results indicate that the vortices of the feet and ventral side of the trunk mainly contribute to the increase and decrease in the horizontal UUS velocity.